Emotional intimacy experiences and challenges of selected Filipino elderly couples - Bernardo, Rowena T.; Hizon, Evalyn Guzman (2012)
ABSTRACT The purpose of this study was to determine the experiences and challenges on emotional intimacy of selected Filipino elderly married couple. Another aim was to examine their emotional intimacy determined in terms of: (a.) Breadth; (b.) Openness; and (c.) Depth. Both quantitative and qualitative methods were applied. Using purposive sampling approach, survey questionnaires were administered to 60 participants from Metro Manila who are elderly (60 and above years), married and living together with their spouses. Thirty were wives and thirty were husbands, not necessarily married to each other. The questionnaire pertained to 24 statements regarding emotional intimacy which was sub-divided into categories referring to the three dimensions namely breadth, openness, and depth. Furthermore, a focus group discussion comprising of three sets were also conducted to strengthen the findings from the survey and also address the correlation of length in years married and emotional intimacy among the elderly married couples who participated. The results showed that emotional intimacy of Filipino elderly married couples in terms of breadth, openness, and depth were strong during the latter stage of marriage as supported by Western literatures. Their wives' respondents fared much higher with the openness and depth aspect of emotional intimacy whereas the husbands scored higher in the breadth or shared activities together. This also implied that wives have a different notion of emotional intimacy than the husbands. Likewise, the focus group discussions revealed that anticipating spouse's thoughts without them expressing it was more crucial to the wives' definition of emotional intimacy than the husbands. Moreover, the couples' emotional intimacy was apparently strongest during the latter stages as compared to the middle stages of marriage as both husbands and wives shared. This study has social and methodological implications and is beneficial not only to married couples but also the academe, other family life educators, counselors, and even single individuals who are aspiring to get married someday.
"April 2012."
Thesis (M.F.L.C.D.)--University of the Philippines Diliman.
Keywords: Intimacy (Psychology).; Marriage -- Philippines